Mining flies (Diptera: Agromyzidae) – phytophages of honeysuckles (Lonicera L.) and snowberries (Symphoricarpos Duhamel) in green areas in Belarus - Volosach, Marina V. (Experimental Biology and Biotechnology, 2020)
According to the results of investigations, carried out in 2016–2019, it was found that in the conditions of green areas of Belarus, honeysuckles (Lonicera L.) and snowberries (Symphoricarpos Duhamel) has been damaged by larvae of 6 species of mining flies (Diptera: Agromyzidae): Aulagromyza cornigera (Griffiths, 1973), Aulagromyza hendeliana (Hering, 1926), Aulagromyza luteoscutellata (de Meijere, 1924), Chromatomyia aprilina (Goureau, 1851), Chromatomyia lonicerae (Robineau-Desvoidy, 1851), Chromatomyia periclymeni (Hendel, 1922). The basic data on trophic relations, the main characteristics of ecology, the distribution in the conditions of Belarus, and the pattern of damages causing by larvae to leaf plates of honeysuckles and snowberries are presented.